Analysis of Right Advertising Strategies in Business to Increase Sales Turnover at Persela Store Lamongan - Dhita Dhora Damayanti (Institute of Computer Science (IOCS), 2019)
Advertising has received a sharp spotlight since the information aspect is an important part of business, effective advertising activities are seen as being able to influence the tendency to consume in society. This study aims to determine the advertising strategy that is currently being implemented by Persela Store Lamongan and to find out which advertising strategies can drive increased sales in Persela Store Lamongan. The method of analysis used is qualitative method using SWOT analysis, IFAS, EFAS, SWOT matrix. The results show that the Advertising Strategy applied by Persela Store Lamongan currently has implemented all Advertising Strategies with the 5M concept, namely: Mission (goal) , Money (money), Message (message), Media (media), Meansurement (measurement) but not yet implemented optimally. Advertising Strategy Analysis using SWOT analysis is the most appropriate in an effort to increase sales turnover at Persela Store Lamongan. ategi SO (Strength Opportunity) with Mission (objectives) and Media (media) strategies. thus showing that Persela Store Lamongan is on the right track by continuing to carry out aggressive strategies to increase sales turnover..